Influence of Romans and Greeks on Western Literature - Dr. Sapana Sharma (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Each piece of literature contains a plethora of insights into the societal, economic, cultural, and philosophical advancements of its respective era. In addition to the aforementioned evidence, it is noteworthy that the dominant belief system of the era exerts a significant impact on both the utilisation of language and the composition itself. This article will examine the impact of Roman and Greek literature on Western literature, and will provide evidence from literary works to support the thesis. The objective of this scholarly article is to investigate the influence of ancient Greek and Roman civilizations on the development of Western literature. The undeniable impact of ancient Greek and Roman literature on Western literature is a well-established fact. The literary traditions of the aforementioned culture have had a significant influence on the manner in which Western writers approach the art of storytelling, language, and style, spanning from epic poetry to drama. The present study aims to analyse the diverse manners in which Greek and Roman literature have impacted Western literature. This will encompass an exploration of the utilisation of mythology, the evolution o